The efficacy of commercially available herbal dentifrices in comparison with conventional dentifrices against two common oral microbes: An In vitro study - Nikesh Thounaojam (Journal of Pharmacy and Bioallied Sciences, 2021)
Background: Mechanical plaque removal is considered the gold standard for controlling and prevention of plaque and gingivitis. The present study was conducted to evaluate the efficacy of commercially available herbal dentifrices in comparison with conventional dentifrices against two of the common oral microbes, namely Streptococcus mutans and Candida albicans. Materials and Methods: To determine the antimicrobial properties of individual dentifrices, the zone of inhibition on the blood agar plates was measured and also disc diffusion method was used for testing the antibacterial properties for which a thin paper disc containing the antimicrobial agent was applied on a culture of bacteria grown on agar media. Each dentifrice was tested in 50% concentration (1:1 dilution [50% w/w] using sterile deionized distilled water/half strength) and 100% concentration (full strength). The blood agar plates were then incubated aerobically at 37°C. The measurement of zone of inhibition was done after 24–48 and 72 h on the underside of the Petri dishes using Vernier calipers. Results: At 50% concentration, Regimen B2 showed the maximum zone of inhibition which was closely followed by Regimen A1 for S. mutans, whereas at 100% concentration, Regimen A1 showed better effects. For C. albicans, it was observed that Dabur red toothpaste showed the significantly higher zone of inhibition at 50% concentration when the concentration was made 100% and also Dabur red toothpaste showed the maximum zone of inhibition. Conclusion: This concluded that the herbal dentifrices are equally and sometimes better than the conventional ones.